The intestinal microbiota of lake anchovy varies according to sex, body size, and local habitat in Taihu Lake, China. Issue 1 (29th November 2019) - Jiang, Min; Xu, Mengyuan; Ying, Congping; Yin, Denghua; Dai, Pei; Yang, Yanping; Ye, Kun; Liu, Kai
Abstract: Lake anchovy ( Coilia ectenes taihuensis ) is a sedentary, dominant fish species that forms an unmanaged fishery in Taihu Lake, eastern China. The environment and developmental stage of lake anchovy are likely important drivers of their gut microbiome, which is linked to host health and development . To investigate the relationship between the gut microbiome and three defined factors (fish sex, fish body size, and the local habitat), high‐throughput sequencing of the 16S ribosomal RNA gene was used to study the microorganisms of 184 fish samples and four water samples collected in Taihu Lake. Four dominant bacterial phyla (Proteobacteria, Firmicutes, Planctomycetes, and Cyanobacteria) were present in all fish samples. We compared the microbial communities of males and females and found that the relative abundance of Corynebacteriaceae was significantly higher in males than in females, while the opposite trend was detected for Sphingomonadaceae . We also discovered that the relative abundance of Firmicutes was positively correlated with fish body size and that the proportions of Proteobacteria and Tenericutes were lower in larger fish than in fish of other sizes. Finally, we found that the difference in microbial richness between eastern and northern Taihu Lake was the most marked. Lake anchovy was rich in Lactobacillus and Clostridium in the eastern site, while those in the northern site had the highest abundance of Sphingomonas and Methylobacterium, suggesting that the local habitat may also influence the intestinal microbiome. These findings will not only help researchers understand the community composition of the intestinal microflora of lake anchovy but also contribute to the protection of fish resources in Lake Taihu and the sustainable use of lake anchovy. Abstract : The present study documented the basic composition of the gut microbiota in lake anchovy ( Coilia ectenes taihuensis ) in Taihu Lake, China, and investigated the potential factors that influence variation in microbial community composition. Three potential factors may affect the intestinal microbiota of lake anchovy: sex, body size, and local habitat.